KETIDAKEFEKTIFAN KALIMAT DALAM ACARA TALK SHOW ROSI EPISODE POLITIK KEBOHONGAN DAN POLITISI SONTOLOYO DI KOMPAS TV - Rachman, Anita Kurnia (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
The study entitles Ineffectiveness of Sentences in Rosi?s Talk Show for episode of Lies Politics and Sontoloyo Politician on Kompas TV has two research focuses, the first focus is to discuss ineffective sentence that are limited to the form of unity and efficiency. The second focus is concerning to the causes of the ineffectiveness on sentences which are limited to contaminant factors, pleonasms and cognitive errors. The method used in this research is qualitative descriptive method because the researcher thoroughly describes ineffective sentences forms and cause factors on ineffectiveness sentences. The object selected in the study is the Rosi?s Talk Show in Politics of Lies and Sontoloyo Politicians? Episode on Kompas TV. The researcher takes the research data in ineffective sentences through transcripts of conversations between speakers and host. The result of study shows that in Rosi?s Talk Show in Politics of Lies and Sontoloyo Politicians? Episode in Kompas TV found ineffective sentences in the form unity and effeciency. Unity is shown by the data with no subject and predicates. Effeciency sentences are indicated by finding data of sentences with double subjects. Based on the cause factors of ineffectiveness sentences, it was found a sentence containing contamination, pleonasms, and cognitive errors. The contamination in the sentence is indicated by the data finding of a sentence that has an irregular and chaotic structure. The pleonasm in a sentence is indicated by the data finding of a sentence with excessive words. The cognitive errors in sentences are indicated by finding data of sentences that do not show a logical meaning relationship.